Sri Lanka : Eighth and Final Review Under the Stand-By Arrangement: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Sri Lanka. (IMF Staff Country Reports; Country Report ;, 2012)
The Eighth and Final Review under the Stand-By Arrangement discusses policies and reforms undertaken by the Sri Lankan authorities. 2012 has shown robust growth in GDP supported by increased agricultural and construction activity. However, a weakening global demand has been an impediment to real GDP growth. The authorities looked forward to continued engagement with the IMF and intended to discuss the possibility of continuing financial support for their economic development agenda under the Extended Fund Arrangement.